THE EFFECT OF MEDIA PUZZLE ON THE ABILITY OF MATHEMATICAL LOGICS IN CLASS 1 STUDENTS - Dini Yeniyansyah; Vera Rieska Andriani; Sukma Murni (IKIP Siliwangi, 2018)
This research is motivated by problems found in SD GIKI in class 1, namely the ability of children's mathematical logic in the low and medium categories . The focus of the research is how the level of students 'mathematical logic ability before using media puzzle and how the level of students' mathematical logic ability after using media puzzle. Is there a significant influence on the use of media puzzles on students' mathematical logic abilities? The purpose of this research is to improve the results and improve the process of students' mathematical logic ability. The method used in this study is the pre-experimental method with the type of one-group pretest-posttest design. The subjects in this study were GIKI Elementary School students in Sukajadi Subdistrict, Bandung City class 1, totaling 11 people. Data collection techniques used in this research is to test and observation. The data processing technique used in this study uses SPSS 18.0. The average score of students' mathematical logic ability at pretest was 12 , 27 and increased to 25.73 at the posttest. The results showed that there were significant effects of using media puzzles on the mathematical logic ability of grade 1 students of SD GIKI . This is indicated by the increasing ability of students in compiling numbers in the category of large order to small, small to large, comparing numbers and classifying and solving problems